PENGEMBANGAN MEDIA KONKRET BERBENTUK VELG RUJI ENERGI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - Endaryati, Sri Adhi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
Science subjects at the elementary level are often considered difficult because of the amount of material that students must read and understand. Therefore, researchers conducted media development that was able to foster student motivation towards science learning. Concrete media "Velg Ruji Energi" is designed to encourage students to actively learn and provide a sense of fun in order to easily instill the concept of motion energy in students. This media is made from used items, namely spoke wheels, dynamos, lights, propellers from number plates and wheel spinners. When rotated, the wheels will rotate (motion energy) to produce electrical energy in the dynamo. The lamp connected to the dynamo will light up (light energy). The propeller also rotates when the wheels rotate to produce motion / wind energy. The results of using this media show that the percentage of student motivation increased from 54.38% to 76.25%. Student learning outcomes have also increased, the original learning average of 53.75 increased to 81.88. The completeness of learning outcomes has also increased from 18.75% to 87.50% after using the "Energy Ruji Wheel" media. Based on this data, it can be concluded that the development of concrete media in the form of "Energy Ruji Wheels" can increase student motivation and learning outcomes in the material of applying the concept of motion energy.